Systematic literature review of adopting eHealth in pharmaceutical care during COVID-19 pandemic: recommendations for strengthening pharmacy services - Cen, Zhi Feng (2022)
Objectives The study aimed to determine how eHealth was adopted in pharmaceutical care (PC), the outcome reported and the contextual factors. Design Systematic literature review in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Data sources Literature was searched in six databases including PubMed, Scopus, Medline, Web of Science, Science Direct and China National Knowledge Infrastructure. Eligibility criteria Studies which reported the usage experiences of eHealth in any aspects of PC by pharmacists during the COVID-19 pandemic, written in English or Chinese, and published in peer-reviewed journals between December 2019 and March 2022 were included. Opinion articles, conference abstracts, correspondence, letters and editorials were excluded. Data extraction and synthesis The literature search was completed on 15 April 2022. Two researchers independently conducted the literature search and extracted the data into an Excel table informed by the logic model with the key components of goals, input, activities, output and contextual factors. Results Forty-three studies were included in this review. During the COVID-19 pandemic, hospital pharmacists, community pharmacists and specialist pharmacists in 17 countries continued to educate, consult, monitor and manage the patients and the general public via phone calls, videoconferences, mobile applications, social media, websites and/or enhanced interoperability of electronic medical records. Assuring the continuity of pharmacy care, reduced need for hospital visits, and improved work accuracy and efficiency were the benefits of eHealth mostly reported. Contextual factors affecting the adoption of eHealth were multifaceted, prompting supporting actions at the levels of government, hospital/pharmacy, pharmacists and patients. Conclusion This study revealed the wide adoption of eHealth in PC during the pandemic and the emerging evidence for its importance. Proper adoption of eHealth will help reshape the mode of pharmacy services to ensure continuity, quality and efficiency of care amid the challenges of the pandemic. PROSPERO registration number CRD42022299812.